2009
DOI: 10.1039/b911457b
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of atmospheric clusters: HNO3–HCl–H2O

Abstract: Nitric acid, hydrochloric acid and water can form stable aggregates with atmospheric implications, for instance at the surface of polar stratospheric clouds. The structure, stability and chemical properties of these ternary complexes are studied by means of high level theoretical calculations (hybrid DFT B3LYP method along with aug-cc-pVQZ basis set). From the many possible systems that these molecules could form, only 15 are found to yield stable structures, well characterized by a minimum in their potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…It has been shown by Gomez et al for one of the ternary complexes studied also in this article that the counterpoise-corrected surface intermolecular distances are a little longer than the values evaluated by the standard gradient optimization. 33 This difference was found to be 3 Â 10 À3 Å with B3LYP/aug-cc-pVQZ. Furthermore, it was reported by Hobza et al for the water dimer that this difference gets smaller with larger basis set.…”
Section: Computational Detailsmentioning
confidence: 96%
“…It has been shown by Gomez et al for one of the ternary complexes studied also in this article that the counterpoise-corrected surface intermolecular distances are a little longer than the values evaluated by the standard gradient optimization. 33 This difference was found to be 3 Â 10 À3 Å with B3LYP/aug-cc-pVQZ. Furthermore, it was reported by Hobza et al for the water dimer that this difference gets smaller with larger basis set.…”
Section: Computational Detailsmentioning
confidence: 96%
“…[22][23][24] Go´mez et al 22 reported fifteen structures characterized by true minima located on the IPES, the NC1W-1 aggregate being the most stable one among them. These structures are especially suitable for studying proton transfer parameter variations in the smallest clusters.…”
Section: Description Of the Systemsmentioning
confidence: 99%
“…This fact was also found in previous papers studying ternary clusters. 22,23 Finally, the third factor involved in proton transfer in HNO 3 is related to the existence of a proton donor acting over the acidic oxygen atom, and also to which molecule that donor may be. For instance, proton transfer does not occur when the proton donor is water, as in NC4W-5 or NC4W-1, whereas in NC4W-4 a HCl donor on the acidic oxygen has a marked effect, making r PT become positive.…”
Section: Proton Transfermentioning
confidence: 99%
See 2 more Smart Citations